Effectiveness of Lactobacillus acidophilus as Probiotic in Cantaloupe (Cucumis Melo) Juice Fermentation - N. P. Minh (Journal of Global Pharma Technology, 2019)
Cantaloupe is one of the most consumed fruit crops worldwide specially in Viet Nam due to its pleasant flavour and nutritional value. Cantaloupe is highly perishable, due to its high moisture content. Lots of cantaloupes rot away in the farmland. The production of freshly cantaloupe juice is a best way to raise the merchandise rate of cantaloupe and to prolong its product shelf-life during consumption. Lactic acid fermentation increases the shelf life of cantaloupe juice and also enhances various beneficial properties, including nutritive value and flavours. Objective of this study focused on the effect of Lactobacillus acidophilus as probiotic in cantaloup (Cucumis Melo) juice production. Different technical parameters such as the initial soluble solid content (8.0, 8.5, 9.0, 9.5, 10.0 oBrix), Lactobacillus acidophilus innoculum size (1.0, 1.5, 2.0, 2.5, 3.0 g/L), fructo-oligosaccharide (0.5%, 1.0%, 1.5%, 2.0%, 2.5%) were examined during fermentation at 37oC in 48 hours. Results showed that the best fermented juice quality would be achieved by the initial soluble solid content 9.5oBrix, Lactobacillus acidophilus innoculum size 2.0 g/L, fructo-oligosaccharide 2.0%.Keywords: Cantaloup, Lactobacillus acidophilus, Probiotic, Juice, Fructo-oligosaccharide, Innoculum.